THE CHARACHTERISTICS OF PROBIOTIC DRINK BASED ON MORINGA LEAVES JUICE - Dewi Desnilasari; Wawan Agustina; Devry Pramesti Putri; Ade Chandra Iwansyah; Woro Setiaboma; Enny Sholichah; Ainia Herminiati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
Moringa (Moringa oleifera) leaves are rich in minerals, vitamins and other essential phytochemicals. This study evaluated the effect of addition skim milk powder levels to the physicochemical, microbiology, antibacterial, and antioxidant properties of probiotic drink based on Moringa leaves juices. The probiotic drink was fermented by Lactobacillus casei FNCC 00090 with different level of skim milk powder (0, 3, 5, and 7%). The results showed that supplementation skim milk powders significantly affected the color of the probiotic product. The higher level of skim milk powders the lighter, greener, and more yellow (P<0.05). The higher concentration of skim milk affected the higher of pH and lactic acid content. The amount of probiotic among the treatment was not significantly different. The addition 7% skim milk powder produced the highest protein content, antibacterial activity, phenolic content, and antioxidant activity. Protein content of the best product was 2.65%, antibacterial activity: 14.50±1.80 mm (zone inhibition of .E coli) and 35.33±4.16c mm (zone inhibition of S. aureus), phenolic content 0.2410±0.0054 mg equivalent galic acid/ml sample and antioxidant activity 75.18±1.45%. The probiotics drink based on Moringa leaves juices has the potential to be developed as a functional drink.